Coffee farmers’ perception of climate change trends in Gimbi district, Western Ethiopia - Chemeda, Beshea Abdissa; Senbeta, Feyera; Birhane, Emiru (Discover Sustainability, 2025)
Climate change and variability pose substantial threats to rain-fed agriculture, critically impacting the livelihoods of rural communities in Ethiopia. The Gimbi District, recognized for its high agricultural potential within the West Wellega Zone, faces severe repercussions from recurrent droughts attributable to climate change. This study critically examines the perceptions of coffee farmers regarding climate change and its consequential effects on food crop production within the Gimbi District. Employing a multistage sampling method, 402 coffee farmers were selected across six kebeles. Additionally, areal gridded surface monthly rainfall and temperature data spanning from 1990 to 2020 were sourced from the Ethiopian Meteorological Institute. The finding reveals that 92% of coffee farmers perceived significant unpredictability in rainfall during the study period. Furthermore, 84% of respondents noted an increase in temperature, while 10% observed a decrease. The modified Mann–Kendall trend test indicated a decline in rainy season rainfall by 69 mm per decade. Concurrently, mean annual temperature exhibited a statistically significant increase (p < 0.001) of approximately 0.31 °C per decade, aligning with the farmers' perceptions. In response to the adverse impacts of climate change, farmers have implemented diverse adaptation strategies, including soil and water conservation as well as crop and livestock management practices. This study underscores the critical need for enhanced adaptive capacities to mitigate the detrimental effects of climate variability on rain-fed agriculture. The alignment between farmers' perceptions and empirical meteorological data further emphasizes the urgency of developing resilient agricultural practices.